Embryogenic potential of the callus of gabirobeira, Campomanesia adamantium (Cambess) O. Berg - Marieli Rossato; Pedro Vitor Schumacher; Antônio Paulino da Costa Netto; Vanessa Cristina Stein; Edésio Fialho dos Reis; Marlúcia Souza Pádua Vilela; Luciano Vilela Paiva (Acta Scientiarum. Biological Sciences, 2019)
Campomanesia adamantium is a native plant species of Brazilian Cerrado with diverse economic potential and great medicinal importance. Its sexual propagation is impaired by the recalcitrance of its seeds, which prevents effective and profitable propagation. With the purpose of establishing commercial crops and minimizing the extractive use of vegetal resources, the aim of the present study was to induce embryogenic calli in nodal segments of gabirobeira, and to determine and characterize their embryogenic phase through the establishment of a growth curve based on cellular characteristics. Calli were induced using nodal segments inoculated in WPM culture medium without the addition of hormones (control) and with different concentrations of 2,4-D, IAA, IBA, NAA or picloram. Cytochemical and SEM analyses revealed cellular characteristics of the formation of meristematic centers that indicated 4.14 μM of picloram to be the best treatment for induction of embryogenic calli, and demonstrating their embryogenic potential. The treatment was used to establish a callus growth curve, from which it was inferred that calli should be transferred to new culture media on the 28th day to maintain cell viability